An anthology of Beowulf criticism - Nicholson, Lewis E. ([Notre Dame, Ind.] : University of Notre Dame Press, 1963)
An anthology of criticism on the early medieval masterpiece. The contributions to this anthology are arranged chronologicall according to the date of the criticism's first publication.
The Christian coloring in the Beowulf / F.A. Blackburn -- The heroic age, an excerpt / H. Munro Chadwick -- The ideal of kingship in Beowulf / Levin L. Schücking -- Beowulf: the monsters and the critics / J.R.R. Tolkien -- The religious principle in Beowulf / Marie Padgett Hamilton -- Beowulf / Kemp Malone -- Beowulf and Christian allegory: an interpretation of Unferth / Morton W. Bloomfield -- The doctrine of charity in mediaeval literary gardens: a topical approach through symbolism and allegory / D.W. Robertson, Jr. -- The oral-formulaic character of Anglo-Saxon narrative poetry / Francis p. Magoun, Jr. -- Beowulf and the Liturgy / Allen Cabaniss -- Beowulf's three great fights / H.L. Rogers -- Good and evil: light and darkness: joy and sorrow in Beowulf / Herbert G. Wright -- Sapientia et fortitudo as the controlling theme of Beowulf / R.E. Kaske -- Sutton Hoo and Beowulf / C.L. Wrenn -- Beowulf -an allegory of salvation? / M.B. McNamee -- The Beowulf poet / Paull F. Baum -- Patristics and Old English literature: notes on some poems / Morton W. Bloomfield -- The Christian perspective in Beowulf / Margaret E. Goldsmith.
"NDP27."
Includes bibliographical references.
Print version record.
JSTOR
Keywords: Beowulf; Beowulf; Beowulf; Beowulf; Beowülf; Beowulf; Beowulf, -- King of the Geats; Epic poetry, English (Old) -- History and criticism; Monsters in literature; Dragons in literature; Heroes in literature; Poésie épique anglaise (vieil anglais) -- Histoire et critique; Monstres dans la littérature.; Dragons dans la littérature.; Héros dans la littérature.; Dragons in literature; Epic poetry, English (Old); Heroes in literature; Monsters in literature; Kritik; Beowulf (anoniem); Criticism, interpretation, etc